Analysis of the Longest Distances Run by the Best Soccer Players at the FIFA World Cup in Brazil in 2014 - Łukasz Bojkowski; Jerzy Eider; Robert Śliwowski; Andrzej Wieczorek (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2015)
The aim of the study was, among other things, to characterise the maximum distance run by the four best teams in the FIFA World Cup in Brazil, including individual tactical formations and players who played for at least 90 minutes in the whole tournament. In total, the highest results of 68 players were established. In the analysis data obtained using Castrol Performance Index method were used. The mean maximum distance run by players of the tournament semi-finalist teams in the 24 analysed games was 11.63 km. The mean by the analysed defenders was 11.75 km, whereas for midfielders it was 12.02 km, for forwards – 11.02 km, and for goalkeepers – 5.65 km. In group of all 68 respondents soccer players a distance of over 15 km in one game was obtained by Bastian Schweinsteiger, Thomas Müller and Lucas Biglia.